2010
DOI: 10.1016/j.neuroimage.2009.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Three stages of facial expression processing: ERP study with rapid serial visual presentation

Abstract: Electrophysiological correlates of the processing facial expressions were investigated in subjects performing the rapid serial visual presentation (RSVP) task. The peak latencies of the event-related potential (ERP) components P1, vertex positive potential (VPP), and N170 were 165, 240 and 240 ms, respectively. The early anterior N100 and posterior P1 amplitudes elicited by fearful faces were larger than those elicited by happy or neutral faces, a finding which is consistent with the presence of a ‘negativity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

75
470
12
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(568 citation statements)
references
References 75 publications
75
470
12
11
Order By: Relevance
“…In contrast to several previous studies, we did not find the "threat gist" effect on P1 that is thought to reflect the coarse extraction of fearful information (e.g., Luo et al, 2010;see Vuilleumier & Poutois, 2007 for a review). We also did not reproduce the early leftlateralized fear effect around 80ms reported by Neath and Itier (2015), although the exact reason why remains unknown.…”
Section: Fearful Expression Processing: It's Not That Early and It's contrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to several previous studies, we did not find the "threat gist" effect on P1 that is thought to reflect the coarse extraction of fearful information (e.g., Luo et al, 2010;see Vuilleumier & Poutois, 2007 for a review). We also did not reproduce the early leftlateralized fear effect around 80ms reported by Neath and Itier (2015), although the exact reason why remains unknown.…”
Section: Fearful Expression Processing: It's Not That Early and It's contrasting
confidence: 99%
“…Therefore this effect has been suggested to reflect enhanced processing of emotionally salient faces in general or of threatening faces in particular (i.e., fearful and angry) in temporo-occipital areas possibly including occipital gyrus, fusiform gyrus and Superior Temporal Sulcus regions (Schupp et al, 2004). The current view is that the EPN reflects more in depth appraisal of the emotion, some form of semantic stage where the meaning of the emotion is extracted (Luo et al, 2010;Vuilleumier & Pourtois, 2007). Some studies have suggested that the EPN reflects the neural activity related to the processing of the emotion that is superimposed onto the normal processing of the face.…”
Section: Early Event-related Potentials In Facial Expression Researchmentioning
confidence: 90%
See 1 more Smart Citation
“…In fact, the ERP literature reports early emotion effects in 22 face perception at a very early point in time, namely in the time window of N1/P1 (e.g., Jetha et al, 23 2012; Luo et al, 2010). Such early emotion effects may occur when stimuli are highly salient, as in the 24 27 case of fear or anger expressions (Adolphs, 2002).…”
mentioning
confidence: 99%
“…VPP is recorded primarily at frontocentral sites between 140 and 180 ms after face presentation in relation to the face structural encoding stage that precedes the processing of emotional recognition (Jeffreys, 1996;Joyce & Rossion, 2005;Rossion et al, 1999;Yuan, Guan, et al, 2011). Differences between emotions and neutral faces (Luo, Feng, et al, 2010), and among different emotions (Williams, Palmer, et al, 2006) have been found in VPP amplitudes.…”
Section: Introductionmentioning
confidence: 98%